Food and nutrition information guide - Szilard, Paula (Libraries Unlimited, 1987)
This reference source is devoted to materials on human nutrition, dietetics, food science and technology, and related subjects such as food service. It is intended to assist researchers, students, professionals, and librarians assess the literature in nutrition. It covers chiefly English-language materials published in the last 10 years. Older materials are included if they are currently useful. Material on animal nutrition is omitted except when useful to those interested in human nutrition. Most citations listed are annotated and those without annotations were verified for bibliographic information, but the author was not able to easily locate them for evaluation. However they were considered potentially useful and included. Subject, and title/author indexes and addresses of organizations and prices of publications are also included